METHODOLOGICAL REQUIREMENTS FOR ORGANIZING OPEN CLASSES IN THE HIGHER EDUCATION SYST (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, open classes conducted by medical educational institutions in alldirections, requirements for their implementation, plan, methodology, guidelines for conductingopen classes, and the importance of ensuring the quality of education rni and its importance arehighlighted. Information about the possibilities, disadvantages and advantages of conducting openclasses in the educational system is presented